Anthropometric Measurement of Hand Dimension and Their Correlation with Height in Undergraduate Students of a Medical College in Nepal - Shrestha, Subina; KC, Sudikshya (Journal of Lumbini Medical College, 2020)
Introduction: Height is important for determination of basic energy requirement, standardization and identification. It is also useful for measuring physical capacity and adjusting drug dosages. Sometimes the exact height cannot be determined directly because the patient is unable to stand as a result of neuromuscular weakness, deformities of axial skeleton, loss of lower limbs and in case of amputation. Forensic investigations of skeletal remains also face the problems. Under such circumstances, height can be estimated by hand dimensions. Methods: Hand dimensions and height were measured on 239 medical students in the Department of Anatomy using standard instruments. Among them 120 were females and 119 were males. Correlation between height and hand dimensions was studied. Regression equation was derived for estimation of height from hand dimensions. Results: The correlations between height and hand dimension were statistically significant in both genders (p<0.05). The Pearson correlation between height and hand length was 0.616 and between height and hand breadth was 0.353 in males. Those coefficients for females were 0.706 and 0.198 respectively. Regression equations were formulated for height with hand length in males and females. Conclusion: Height can be predicted from hand length. Hand length showed moderate (males) to strong (females) positive correlation with statistical significance whereas hand breadth showed weak positive correlation with statistical significance.